Three years with a knife stuck in the brain - Dias Filho, Luiz Coutinho; Caetano de Barros, Alex; Félix da Mota, Marina (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2014)
Cranial stabbing injuries penetrating the brain are not commonly encountered. The cases in which the knife is retained constitute a challenge to the neurosurgeon. When a long-term permanence occurs, the reaction to the presence of the foreign body causes adherence to the nervous tissue and a higher risk is expected from the removal. The procedure should be performed with meticulous dissection and minimal oscillation of the blade thus avoiding damage to the adjacent structures. We report a case of a man who remained three years with a knife blade deeply lodged in the brain. After obtaining informed consent, the blade was removed; there were no postoperative complications. To our knowledge, this is the first case in which, after years of permanence, a knife blade was removed from the brain through a craniotomy.
Keywords: Craniotomy; head injuries penetrating; puncture wounds; stab